Single-Chamber Leadless Cardiac Pacemaker in Patients Without Atrial Fibrillation: Findings From Campania Leadless Registry - Russo, Vincenzo; D'Andrea, Antonello; De Vivo, Stefano; Rago, Anna; Manzo, Gianluca; Bocchetti, Antonio; Papa, Andrea Antonio; Giordano, Valerio; Ammendola, Ernesto; Sarubbi, Berardo; Golino, Paolo; D'Onofrio, Antonio; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Little is still known about the clinical performance of single chamber leadless pacemaker (LLPM) in patients without atrial fibrillation (AF) as pacing indication. The aim of our study was to describe the clinical characteristic of patients underwent single chamber LLPM implantation at three tertiary referral centers and to compare the safety and effectiveness of single chamber LLPMs among patients with or without atrial fibrillation. Materials and Methods: All consecutive patients who underwent LLPM implantation at three referral centers were analyzed. The indications to LLPM in real-world setting were described. The study population was divided into two groups according to AF as pacing indication. We assessed the procedure-related complications; moreover, we compared syncope, cardiac hospitalization, pacemaker-syndrome and all-cause death recurrence during the follow-up between patients with and without AF as pacing indication. Results: 140 consecutive patients (mean age 76.7 11.24, males 64.3%) were included in the study. The indication to LLPM implantation was permanent AF with slow ventricular response (n: 67; 47.8%), sinus node dysfunction (n: 25; 17.8%), third atrio-ventricular block (AVB) (n: 20; 14.2%), second-degree AVB (n: 18; 12.8%) and first degree AVB (n: 18; 12.8%). 7 patients (5%) experienced peri-operative complications with no differences between AF vs no AF groups. During a mean follow-up was 606.5 265.9 days, 10 patients (7.7%) died; 7 patients (5.4%) reported cardiac hospitalization; 5 patients (3.8%) experienced syncope; no patients showed pacemaker-syndrome. No significant differences in clinical events between the groups were shown. The Kaplan-Maier analysis for the combined endpoints did not show significant differences between AF and non-AF group (HR: 0.94, 95% C.I. 0.41- 2.16; P= 0.88) Conclusion: Our real-world data suggest that LLPM may be considered a safe and reasonable treatment in patients without AF in need of pacing. Further studies are needed to confirm these preliminary results.